Problems of Mental Health: Growth of Mental Illness Between Young People and the Population After the Pandemy of Covid-19 - qizi, Otamurodova Khurshidabonu Bakhtiyor; oʻgʻli, Otamurodov Azizbek Bakhtiyor (American Journal of Bioscience and Clinical Integrity, 2025)
The COVID-19 pandemic not only caused a global public health emergency but also led to profound consequences on the mental well-being of populations worldwide. Social isolation, prolonged lockdowns, economic instability, and fear of infection created unprecedented psychological stress. This study investigates the surge of mental health disorders, particularly among adolescents and young adults, during and after the pandemic. By analyzing global and regional data, the research highlights the increase in depression, anxiety, post-traumatic stress disorder (PTSD), and substance abuse, while also identifying gaps in mental healthcare services. The findings stress the urgent need for integrated mental health strategies, accessible psychological services, and public education to mitigate long-term consequences. The COVID-19 pandemic represented one of the greatest global public health crises of the twenty-first century, and its consequences extended well beyond physical illness. It significantly disrupted the mental well-being of populations across age groups and geographic regions. Young people, particularly adolescents and university students, were disproportionately affected due to academic disruptions, social isolation, excessive reliance on digital technology, and the uncertainty of their future prospects. Adults, meanwhile, suffered heightened stress as a result of unemployment, economic instability, bereavement, and social disconnection. This article aims to analyze the multifaceted growth of mental health disorders in both young people and the broader population following the pandemic. The study synthesizes available international evidence and contextualizes findings within the regional experience of Central Asia, with a particular focus on post-pandemic psychosocial shifts, increased incidence of depression, anxiety, post-traumatic stress, and the strain on healthcare systems. Moreover, it emphasizes the pressing need for governments and institutions to prioritize mental health policy, expand access to services, strengthen resilience-building strategies, and combat stigma.